2017
DOI: 10.1111/1462-2920.13629
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium ulcerans toxin, mycolactone may enhance host‐seeking and oviposition behaviour by Aedes aegypti (L.) (Diptera: Culicidae)

Abstract: The ecological functions of many toxins continue to remain unknown for those produced by environmental pathogens. Mycobacterium ulcerans, the causative agent of the neglected tropical disease, Buruli ulcer, produces a cytotoxic macrolide, mycolactone, whose function(s) in the environment remains elusive. Through a series of dual-choice behaviour assays, they show that mycolactone may be an interkingdom cue for the yellow fever mosquito, Aedes aegypti, seeking blood-meals as well as oviposition sites. Results p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…A recent study in our laboratories demonstrated mycolactone influences behavior of the yellow fever mosquito, Aedes aegypti aegypti, (L.) (Diptera: Culicidae) (Sanders et al, 2017), which occurs in similar environments (Garnham et al, 1946;Christophers, 1960) as M. ulcerans (Williamson et al, 2012). In the study, 29% more were attracted to blood-feeders treated with 1.0 µg/ml mycolactone compared to control feeders.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…A recent study in our laboratories demonstrated mycolactone influences behavior of the yellow fever mosquito, Aedes aegypti aegypti, (L.) (Diptera: Culicidae) (Sanders et al, 2017), which occurs in similar environments (Garnham et al, 1946;Christophers, 1960) as M. ulcerans (Williamson et al, 2012). In the study, 29% more were attracted to blood-feeders treated with 1.0 µg/ml mycolactone compared to control feeders.…”
Section: Introductionmentioning
confidence: 70%
“…All experiments were conducted under the laboratory conditions previously described (Sanders et al, 2017). For the larval growth/ survivorship assay, 40 Ae.…”
Section: Larval Growth/survivorship Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The traumatized skin should initially be colonized by MU , a phenomenon that could naturally happen during repetitive contacts with the risk environments such as water bodies or contaminated biofilms [ 1 , 17 , 28 ]. Furthermore, in behavioral study with Aedes aegypti , Sanders et al [ 50 ] suggested that if a biofilm of MU was on a person, the bacteria may be attracting mosquitoes which in return would lead to a puncture insertion of MU as recently reported by Wallace et al [ 28 ]. Although mechanical transmission of MU stands as a common mechanism that could correlate transmission studies from both Africa and Australia, Williamson et al [ 30 ] recently established that abrasions (trauma) of the skin in Guinea pig models and subsequent application of MU are not sufficient enough to cause an ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Other experimental studies suggest that mycolactone may serve as a potential attractant for mosquitoes, thereby facilitating M . ulcerans transmission [ 90 , 91 ]. Ultimately, further experimental and observational studies are needed to establish vector competence.…”
Section: Mosquitoes In Mycobacterium Ulcerans Transmissionmentioning
confidence: 99%